Relative biological effectiveness of carbon ions in a rat prostate carcinoma in vivo: comparison of 1, 2, and 6 fractions - Karger, Christian; Peschke, Peter; Scholz, Michael; Huber, Peter E.; Debus, Jürgen (International journal of radiation oncology, biology, physics, 2013)
Purpose - To determine the relative biological effectiveness (RBE) and the effective α/β ratio for local tumor control of a radioresistant rat prostate tumor (Dunning subline R3327-AT1) after 6 fractions of carbon ions and photons. - Methods and Materials - A total of 82 animals with tumors in the distal thigh were treated with 6 fractions of either photons or carbon ions, by use of increasing dose levels and a 2-cm spread-out Bragg peak. Endpoints of the study were local control (no tumor recurrence within 300 days) and volumetric changes after irradiation. The resulting values for dose at 50% tumor control probability were used to determine RBE values. Including data for 1 and 2 fractions from a previous study, we estimated α/β ratios. - Results - For 6 fractions, the values for dose at 50% tumor control probability were 116.6 ± 3.0 Gy for photons and 43.7 ± 2.3 Gy for carbon ions and the resulting RBE was 2.67 ± 0.15. The α/β ratio was 84.7 ± 13.8 Gy for photons and 66.0 ± 21.0 Gy for carbon ions. Using these data together with the linear-quadratic model, we estimated the maximum RBE to be 2.88 ± 0.27. - Conclusions - The study confirmed the increased effectiveness of carbon ions relative to photons over the whole dose range for a highly radioresistant tumor. The maximum RBE below 3 is in line with other published in vivo data. The RBE values may be used to benchmark RBE models. Hypoxia seems to have a major impact on the radiation response, although this still has to be confirmed by dedicated experiments.